O Kae? An Autoethnographic Dramaturgy Through A Deliberate Incommensurability - Seane, Warona (Department of Drama, 2020)
This study focuses on the erasure of the black woman from the mainstream theatre space of South Africa as a provocation towards the creation of a dramaturgical process that pivots around the notion of 'deliberate incommensurability' as a catalyst for exploration. 'deliberate incommensurability' is a term I have coined myself as it suggests an agency in the black woman as subject and object of study. I suggest the requirement for an autoethnographic inquest in carrying out the research, as the methodology used in the creation of the processes and products of the study was Practice as Research (PaR). The methodology uses the modes of translation and literary studies in order to unpack the myriad ways in which the representation of the black female has effectively been an erasure of her presence. I detail four points of origin for the study drawn primarily from Gayatri C. Spivak and Toni Morrison. In addition, the study interrogates the processes towards creating O Kae? - a performance installation that evaluates the importance of opacity towards the self-representation of the Other in an attempt to discover an alternative aesthetic and creative praxis for myself.